Prilagodljiva delovna okolja in njihova vloga v izobraževanju odraslih - Radovan, Marko (AS. Andragoška spoznanja, 2024)
Using data from the 2021 Active and Inactive Population Survey, we examined how the type of employment, company size and working conditions influence participation in adult education. We found that people who are employed full-time or on fixed-term contracts are more likely to participate in adult education than those on permanent or part-time contracts. Flexible working hours and the possibility of remote work signif icantly increase participation, while shift work has a negative impact. We conclude that employment characteristics and flexibility signif icantly influence participation in adult education. However, it is important to point out that flexible working arrangements can also have negative consequences, such as increased feelings of loneliness, a possible work-life imbalance and diff iculties in maintaining constant engagement at work. With this in mind, we recommend the implementation of targeted policies and measures to promote participation in adult education in various work environments and economic sectors. It is important to consider the potential disadvantages when introducing flexible working arrangements so as not to compromise the health and well-being of employees.
Keywords: adult education; delo na daljavo; fleksibilni načini dela; flexible working; izobraževanje odraslih; izobraževanje zaposlenih; participation in adult education; teleworking; udeležba odraslih v izobraževanju; work; workplace characteristics; značilnosti delovnega mesta